"Dov'è la sinistra?" Hemispatial neglect in stroke - Luukkainen-Markkula, Riitta (fi=Turun yliopisto|en=University of Turku|, 2012)
As long as the incidence of stroke continues to grow, patients with large right hemisphere lesions suffering from hemispatial neglect will require neuropsychological evaluation and rehabilitation. The inability to process information especially that coming from the left side accompanied by the magnetic orientation to the ipsilesional side represents a real challenge for rehabilitation. This dissertation is concerned with crucial aspects in the clinical neuropsychological practice of hemispatial neglect. In studying the convergence of the visual and behavioural test batteries in the assessment of neglect, nine of the seventeen patients, who completed both the conventional subtests of the Behavioural Inattention Test and the Catherine Bergego Scale assessments, showed a similar severity of neglect and thus good convergence in both tests. However, patients with neglect and hemianopia had poorer scores in the line bisection test and they displayed stronger neglect in behaviour than patients with pure neglect. The second study examined, whether arm activation, modified from the Constraint Induced Movement Therapy, could be applied as neglect rehabilitation alone without any visual training. Twelve acute- or subacute patients were randomized into two rehabilitation groups: arm activation training or traditional voluntary visual scanning training. Neglect was ameliorated significantly or almost significantly in both training groups due to rehabilitation with the effect being maintained for at least six months. In studying the reflections of hemispatial neglect on visual memory, the associations of severity of neglect and visual memory performances were explored. The performances of acute and subacute patients with hemispatial neglect were compared with the performances of matched healthy control subjects. As hypothesized, encoding from the left side and immediate recall of visual material were significantly compromised in patients with neglect. Another mechanism of neglect affecting visual memory processes is observed in delayed visual reproduction. Delayed recall demands that the individual must make a match helped by a cue or it requires a search for relevant material from long-term memory storage. In the case of representational neglect, the search may succeed but the left side of the recollected memory still fails to open. Visual and auditory evoked potentials were measured in 21 patients with hemispatial neglect. Stimuli coming from the left or right were processed differently in both sensory modalities in acute and subacute patients as compared with the chronic patients. The differences equalized during the course of recovery. Recovery from hemispatial neglect was strongly associated with early rehabilitation and with the severity of neglect. Extinction was common in patients with neglect and it did not ameliorate with the recovery of neglect. The presence of pusher symptom hampered amelioration of visual neglect in acute and subacute stroke patients, whereas depression did not have any significant effect in the early phases after the stroke. However, depression had an unfavourable effect on recovery in the chronic phase. In conclusion, the combination of neglect and hemianopia may explain part of the residual behavioural neglect that is no longer evident in visual testing. Further research is needed in order to determine which specific rehabilitation procedures would be most beneficial in patients suffering the combination of neglect and hemianopia. Arm activation should be included in the rehabilitation programs of neglect; this is a useful technique for patients who need bedside treatment in the acute phase. With respect to the deficit in visual memory in association with neglect, the possible mechanisms of lateralized deficit in delayed recall need to be further examined and clarified. Intensive treatment induced recovery in both severe and moderate visual neglect long after the first two to first three months after the stroke.